Les contes folkloriques dans la dramaturgie symboliste: francophone et slave (Colloquia Comparativa Litterarum, 2025)
The paper examines the selection, structuring and dramatic rendition of the fairy tale plots in the Francophone and the Slavic symbolist dramas, to point out their typological resemblances and inner richness. The study finds out that rewriting the magic stories and their syncretic approach characterize both theatres and mark out their similitudes. However, the Francophone symbolists attempt to intensify the universal and mystical meaning of the folktales. On the other hand, the Slavic authors insert some national and parodic trends in their plays, strengthen the art synthesis and anticipate, in that way, the dramatic experiments in the European vanguards.